Pengaruh Pendidikan Pada Kinerja Bendahara Dengan Pelatihan Dan Motivasi Sebagai Pemoderasi - Wasasih, Ni Made; Yadnyana, I Ketut; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Financial management in SKPD can not be separated with the function of treasurers, particulary in the preparation of financial account. This research porpused  to obtained the effect on the performance of education towards the treasurers’ performance,and to compatence training and motivation in moderating the influence of  education on treasurer’s performance. The samples was determined by  purposive sampling and it was obtained of 51 respondent.  The data was analyzed  by utilizing Moderation Regression Analysis. This study indicated that the performance of treasurers is effected by education and the effect of education towards the treasurers performance are able to  moderated education on the performance of treasurers
Keywords: education, training, motivation, performance of treasurers